Investigating the influence of vertical moisture integrated flux convergence on rainfall recovery in the Sahel region of West Africa - Teslim Olatunde Adigun; Ayomide Victor Arowolo; Ifeoluwa Adebowale Balogun (Environmental Systems Research)
Abstract The West African Sahel, situated as a semiarid transition area between the Sahara Desert and the savannah subregion, has garnered considerable research interest in recent years due to its distinctive climate characteristics. Of particular focus in this study are the patterns of moisture flux convergence and summer monsoon rainfall in the Sahel, and their interconnected variability. This study aims to enhance our comprehension of the dynamics governing the variation of the West African Monsoon (WAM) through the Vertical Integrated Moisture Flux Convergence. (VIMFC). This study findings reveal a notable upward trend in rainfall within the Sahel region over the past thirty years, primarily attributed to the climate's response to atmospheric warming. Projections indicate that, with future warming, the frequency of rainy days and the occurrence of rainfall are expected to increase in the Sahel. While the dominant circulation systems exhibit no significant deviations, the lower-level wind patterns play a crucial role in transporting moisture from the Atlantic Ocean to the Sahel. Moreover, strengthening of wind patterns at higher altitudes correlates with wetter conditions in the Sahel in the latter decades.